The impact of Covid-19 on South African migrant wage workers and the self-employed - Margareet Visser (International Labour Organization (ILO), 2023)
When Covid-19 struck, the South African government declared some of the strictest lockdowns worldwide. The impact of lockdowns on the working classes was especially severe. Initially many workers were left with no income, leading to warnings that a pandemic of hunger may eclipse the deadliness of the Covid-19 pandemic. Classified as essential workers, farm workers were "lucky enough" to continue working and earning an income. Yet, this paper highlights how Covid-19 regulations exacerbated their vulnerability due to a pre-existing lack of public regulation and enforcement of basic labour and transport regulation in the sector. Apart from farm workers, the paper also discusses how informal workers - in this case taxi drivers - tried to leverage the pandemic to push for closer integration into the agricultural sector to create more sustainable livelihoods for themselves.
Keywords: 330; self employment; migrant workers; COVID-19